Opportunities and Challenges For Halal UMKM in Facing The Development of Digitalization in Indonesia - Zahra, Inas Afifah; Bidhari, Sandhika Cipta; Farhani, Nuraeni Hadiati (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2025)
The development of digitalization in Indonesia has opened up significant transformation space for Micro, Small, and Medium Enterprises (MSMEs), including halal MSMEs which are growing along with increasing public awareness of halal products. Digitalization presents great opportunities in the form of operational efficiency, market expansion, and increased competitiveness through the use of digital platforms, e-commerce, and technology-based payment systems. However, behind these opportunities, halal MSMEs also face complex challenges, such as limited digital literacy, affordability of technological infrastructure, and adaptation to evolving halal regulations and certifications. The method used in this study is a qualitative approach. This study aims to identify strategic opportunities and main obstacles faced by halal MSMEs in the digital era, as well as to formulate policy recommendations that can support the sustainable empowerment of halal MSMEs. The results of this study are expected to be a real contribution to the development of an inclusive and adaptive halal MSME ecosystem to changes in the era of national digitalization.